Ethnolinguistic Vitality of the Iban Language in Iban-dominant and Non-Iban-dominant Areas in Sarawak, Focusing on Language Use and Language Attitudes - Lilly, Metom (UNIMAS, 2025)
The study aimed to investigate the ethnolinguistic vitality of the Iban language in Iban-dominant and non-Iban-dominant areas in Sarawak, focusing on language use and language attitudes. The specific objectives of the study were (1) to identify the Iban respondents’ perceptions of their language use in various domains: the family domains, outside-home domains, as well as social media and new domains; (2) to examine the Iban respondents’ attitudes towards the instrumental value and status of the Iban language in Sarawak; (3) to compare the use of Iban in interactions in the family, outside the home, and social media and new domains, and the attitudes towards Iban in Iban-dominant and non-Iban-dominant areas, and (4) to compare the perceived and observed language use of the participants in Iban-dominant and non-Iban-dominant areas. This study adopted a mixed method incorporating both quantitative and qualitative approaches. Two types of instruments were used in this study: a set of online questionnaires via Google Form developed based on UNESCO’s nine criteria of language vitality/endangerment, and a non-participant observation sheet developed based on Fishman’s (1967) theory of language domains. The questionnaire data were obtained from 1,204 Iban respondents, while the participants for the non-participant observations involved 102 respondents. Five key findings were identified from the study, namely, (1) most respondents learned Iban informally, acquired from their parents; (2) the Iban language is predominantly used at home but faces reduced transmission in non-Iban-dominant areas, especially in interactions involving Iban younger generations; (3) Iban is used to a lesser extent in communication with other ethnic groups (Malay, Bidayuh, Orang Ulu, Chinese, etc.) despite being the largest ethnic group in Sarawak; (4) Iban is the least used language for social and professional interactions in social media and new media domains, in which English emerges as the primary language for communication; and (5) iv locality plays a significant influence on language use and attitudes within the Iban community, particularly emphasising the effect on intergenerational language transmission, religious practices, and communication in various social contexts. The language vitality of Iban can be graded as medium-level, roughly aligned with Grade 5- on the UNESCO framework. While the Iban language maintains a stable speaker base and positive community attitudes, it faces challenges from dominant languages (Malay and English) that restrict its formal and new media use. Its moderate institutional support highlights the need for proactive measures to strengthen education, literacy, and domain expansion to ensure its continued vitality and prevent future endangerment.